Effect of Roundness Error of Inner and Outer Raceway on Rotation Accuracy of Four-point Contact Ball Bearing - Yue Chen; Ming Qiu; Kaiwen Tian; Hui Du; Xu Yang (Jixie chuandong)
Abstract Taking the four-point contact ball bearing as the research object，the research of the rotation accuracy of the four-point contact ball bearing is carried out， and the numerical calculation method of the bearing rotation accuracy considering the roundness error of the inner ring and the outer ring of the bearing is proposed. The radial runout of bearing is used to describe the rotation accuracy. According to the structural characteristics and motion relationship of the four-point contact ball bearing， the mathematical model of the bearing radial runout is constructed，and the program is programmed on Matlab for simulation calculation. The results show that when the harmonic order of the inner raceway is constant， the rotation accuracy of the bearing will decrease with the increase of the harmonic amplitude. When the harmonic order of roundness error of the inner ring is 3，that is，the profile of inner raceway is a triangular circle，the radial runout of the bearing is lowest and the rotation precision of bearing is the highest. The radial runout of the outer ring is the largest when the harmonic order of roundness error of the outer ring is the integral relationship of the number of steel balls. The value of the outer ring radial runout is the smallest when the harmonic order of roundness error of the outer ring is an odd multiple of half the number of steel balls.